2017
DOI: 10.1159/000478892
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Primary Headache Disorders in Kuwait

Abstract: Background: Only an insignificant quantum of data exists on the prevalence of primary headaches among those living in Kuwait. We aimed to determine the prevalence of primary headaches among the Kuwaiti population. Methods: This community-based study included Kuwaiti population aged 18-65 years. Using systematic random sampling, data was collected by the Headache-Attributed Restriction, Disability, Social Handicap and Impaired Participation questionnaire. Responses to the diagnostic questions were transformed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 33 publications
(54 reference statements)
3
16
1
Order By: Relevance
“…Regarding tension headache, there were 17 patients (14.2%) in the control group. This result is lower than the study of Cvetković et al [43] who reported a prevalence of 20.6% in the Croatian population and Al-Hashel et al [44] from Kuwait who diagnosed tension headache in 29.0% of a large 15,523 patients' study.…”
Section: Discussioncontrasting
confidence: 57%
“…Regarding tension headache, there were 17 patients (14.2%) in the control group. This result is lower than the study of Cvetković et al [43] who reported a prevalence of 20.6% in the Croatian population and Al-Hashel et al [44] from Kuwait who diagnosed tension headache in 29.0% of a large 15,523 patients' study.…”
Section: Discussioncontrasting
confidence: 57%
“…In a prior publication, we reported on prevalence of primary headache disorders. In the present study, we further report on the prevalence of episodic migraine stratified by age and gender, characters of migraine in addition to its burden, which was not shown in our previous published paper [ 10 ].…”
Section: Introductionmentioning
confidence: 61%
“…The study sample presented 1.23% of the general population. A flowchart of the participants was published in our earlier paper [ 10 ]. Males represent 51.1% ( n = 7925) of the analyzed sample.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of MOH is estimated between 1% and 3%, making it one of the most common secondary headache disorders 12‐16 . In tertiary headache clinics, about 50% of patients also have medication overuse 17 .…”
Section: Introductionmentioning
confidence: 99%